The Effect of Student Worksheets (LKPD) on Indonesian Language Learning Outcomes in Grade IV Madrasah Ibtidaiyah - Fitriani Fitriani; Sapri Sapri (Journal of General Education and Humanities, 2025)
Learning the Indonesian language in elementary schools often encounters challenges, particularly in fostering active student participation and ensuring comprehension of texts, especially fables. To address this issue, Student Worksheets (LKPD) are designed to enable learners to construct their knowledge through meaningful learning activities independently. This study aims to examine the impact of LKPD implementation on students’ learning outcomes in Indonesian language lessons, focusing on fable texts. A quantitative approach was employed using a one-group pretest–posttest experimental design, involving 25 fourth-grade students from MIS Al-Hidayah Sidodadi as participants. A multiple-choice test served as the primary instrument to measure achievement. The data analysis revealed a significant improvement in learning outcomes after the introduction of LKPD, as evidenced by the paired-sample t-test result showing a significance value (2-tailed) of less than 0.001, which is below the 0.05 threshold. Consequently, the null hypothesis (H₀) was rejected, and the alternative hypothesis (H₁) was accepted. These results align with Bruner’s constructivist theory, which emphasizes the importance of active student engagement in building knowledge through exploration and structured activities. Therefore, the use of LKPD has been proven effective in enhancing students’ learning outcomes in Indonesian language instruction.